2022
DOI: 10.48550/arxiv.2201.06455
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Make Reddit Great Again: Assessing Community Effects of Moderation Interventions on r/The_Donald

Amaury Trujillo,
Stefano Cresci

Abstract: The subreddit r/The_Donald was repeatedly denounced as a toxic and misbehaving online community, reasons for which it faced a sequence of increasingly constraining moderation interventions by Reddit administrators. It was quarantined in June 2019, restricted in February 2020, and finally banned in June 2020, but despite precursory work on the matter, the effects of this sequence of interventions are still unclear. In this work, we follow a multidimensional causal inference approach to study data containing mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Since social media platforms are key drivers of traffic towards far-right websites (together with search engines) ( Chen et al, 2022 ), it is important to note that many of the links towards such websites are made available to the public through bots. Although our findings may point to the automatic removal of bots from political debates as a possible intervention ( Cantini et al, 2022 ), there is evidence that attempts at moderating content can lead to even greater polarization ( Trujillo & Cresci, 2022 ), hence the need for caution when intervening.…”
Section: Discussionmentioning
confidence: 77%
“…Since social media platforms are key drivers of traffic towards far-right websites (together with search engines) ( Chen et al, 2022 ), it is important to note that many of the links towards such websites are made available to the public through bots. Although our findings may point to the automatic removal of bots from political debates as a possible intervention ( Cantini et al, 2022 ), there is evidence that attempts at moderating content can lead to even greater polarization ( Trujillo & Cresci, 2022 ), hence the need for caution when intervening.…”
Section: Discussionmentioning
confidence: 77%
“…Theories from the social, psychological, and behavioral sciences support these empirical results [7] and posit that the efficacy of interventions depends on individual and contextual characteristics [27]. In line with this literature, but in contrast to the platforms' objectives, the interventions recently applied by Twitter and Reddit against toxic users caused a subset of users to become even more toxic and radicalized [11,15,24].…”
Section: The Case For Personalization In Online Moderationmentioning
confidence: 98%
“…As a recent example, when Twitter sent warning messages to dissuade users from posting toxic tweets, all users received the exact same message [15]. However, results on user reactions to moderation interventions showed that different users react in different ways to the same intervention, according to their individual characteristics [22,24]. Theories from the social, psychological, and behavioral sciences support these empirical results [7] and posit that the efficacy of interventions depends on individual and contextual characteristics [27].…”
Section: The Case For Personalization In Online Moderationmentioning
confidence: 99%
See 2 more Smart Citations